Analysis of Slang is Used by Teenagers in Wonokromo Surabaya - Sulistiyani (Penerbit STKIP PGRI Bangkalan, 2016)
Language is one of human communication cues that have an important role in daily life- today. The term of Sociolinguistics is a developing branch of linguistics and sociology which investigates the individual and social variation of language. Just as regional variation of language can give a lot of information about the place the speaker is from, social variation tells about the roles performed by a given speaker within one community, or country. Sociolinguistics is also a branch of sociology in that it reveals the relationship between language use and the social basis for such use. Sociolinguistics differs from sociology of language in that the focus of sociolinguistics is the effect of the society on the language, while the latter's focus is on the language's effect on the society. The data were grouped based on their characteristic. After that the theory from the source book were used to analyze the data. Especially for the data of Indonesian slang word was categorized based on its concepts whether it has the same or not in both the source language and the target language based on the theory. Conducting similar study in the related field or a study with improvement in the methods used in the present research.